COMPARATIVE EFFECT OF ESPRESSO COFFEE AND CAPPUCINO COFFEE ON INSOMNIA IN ADULTS: SYSTEMATIC REVIEW - Lena Maryam; Popi Sopiah; Ria Inriyana (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Insomnia is a disorder that occurs when a person is dissatisfied with the quantity or quality of their sleep. Insomnia can be caused by many things, including disease, environmental conditions, physical activity, mental stress, drugs, and chemicals, caffeine or coffee. Coffee is one of the most frequently consumed drinks throughout the world. Apart from having beneficial activities, caffeine also has detrimental activities, including insomnia and headaches. This study aims: To identify further research through systematic review research that compares the effect of espresso and cappuccino coffee on insomnia in adults. Method: The method used is a systematic review by identifying and evaluating literature with a quantitative research design in accordance with predetermined criteria and feasibility. The databases used include Google Scholar, Pubmed, and Systematic Scholar. Relevant articles underwent quality assessment using the JBI Critical assessment. The keywords entered are